Weakening of the Censorship of the Soviet Power Structures (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This study focuses on the domestic influence of the American media, particularly the Voice of America (USSR), on the collapse of the Soviet Union. In it, the propaganda and propaganda work of the American mass media aimed at overthrowing the communist regime in the Soviet Union, and the determined efforts made in this way; The rise and fall of censorship by Soviet power structures; explores the organization's key role in protecting the Soviet establishment from the influence of the US media.